2013
DOI: 10.1007/s10327-013-0457-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological and genetic diversity of plasmodiophorid-transmitted viruses and their vectors

Abstract: About 20 species of viruses belonging to five genera, Benyvirus, Furovirus, Pecluvirus, Pomovirus and Bymovirus, are known to be transmitted by plasmodiophorids. These viruses have all positive-sense single-stranded RNA genomes that consist of two to five RNA components. Three species of plasmodiophorids are recognized as vectors: Polymyxa graminis, P. betae, and Spongospora subterranea. The viruses can survive in soil within the long-lived resting spores of the vector. There are biological and genetic variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 115 publications
1
26
0
1
Order By: Relevance
“…Olpidium and nematode vectors transmit viruses to a wide range of hosts, particularly vegetable, ornamental and fruit plants, while viruses transmitted by plasmodiophorid vectors have a more limited range of hosts, but are important food crops such as cereals (furo- and bymoviruses), sugar beet and rice (benyviruses), peanut (pecluviruses), and potato (pomoviruses). For more details and comprehensive reviews regarding the vectors and genomes of soil-borne viruses, readers are referred to Brown et al (1995) , Rush (2003) , Rochon et al (2004) , Kühne (2009) , Bragard et al (2013) , Tamada and Kondo (2013) , and Syller (2014) and references therein.…”
Section: Diversities Of Soil-borne Viruses and Their Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Olpidium and nematode vectors transmit viruses to a wide range of hosts, particularly vegetable, ornamental and fruit plants, while viruses transmitted by plasmodiophorid vectors have a more limited range of hosts, but are important food crops such as cereals (furo- and bymoviruses), sugar beet and rice (benyviruses), peanut (pecluviruses), and potato (pomoviruses). For more details and comprehensive reviews regarding the vectors and genomes of soil-borne viruses, readers are referred to Brown et al (1995) , Rush (2003) , Rochon et al (2004) , Kühne (2009) , Bragard et al (2013) , Tamada and Kondo (2013) , and Syller (2014) and references therein.…”
Section: Diversities Of Soil-borne Viruses and Their Vectorsmentioning
confidence: 99%
“…Soil-borne viral diseases are generally difficult to control with conventional chemical or agronomical methods because viruliferous vectors could be widespread underground. In particular, viruliferous resting spores of the zoosporic vectors could be stable and persistent in the infested soil for decades ( Rochon et al, 2004 ; Bragard et al, 2013 ; Tamada and Kondo, 2013 ). Consequently, the disease control-measures are mainly dependent on natural plant resistance resources ( Kanyuka et al, 2003 ; Kühne, 2009 ; McGrann et al, 2009 ; Ordon et al, 2009 ), but in agricultural systems, the emergence of resistance-breaking viruses poses a serious threat to crop production ( Kühne, 2009 ; Tamada and Kondo, 2013 ; Tamada et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic symptoms on leaves are characterized by vein yellowing and necrosis, but can be seldomly observed in the field. The virus is transmitted by the soil-borne plasmodiophoromycete Polymyxa betae that infects the root tissue of sugar beet plants (Keskin, 1964;Tamada and Kondo, 2013). Resting spores can survive in the soil for decades containing infectious virus particles.…”
Section: Introductionmentioning
confidence: 99%
“…BdMoV induces the formation of spherical electron-dense, viroplasm-like inclusion bodies in the cytoplasm of cells (Inouye, 1973;Yamashita et al, 2008). Our molecular study has shown that the genome of BdMoV is similar to that of beet necrotic yellow vein virus (BNYVV) (Hirano et al, 1999), and therefore BdMoV is a tentative species of the genus Benyvirus (Gilmer and Ratti, 2012;Koenig and Lesemann, 2005;Rush, 2003;Tamada, 1999;Tamada and Kondo, 2013).…”
Section: Introductionmentioning
confidence: 82%
“…Thus, it seems unlikely that P. betae is the natural vector of BdMoV. The vector of BdMoV still needs to be determined; however, owing to a similarity in the genome structure and especially the presence of the two transmembrane regions in the RT domain (Adams et al, 2001;Tamada and Kondo, 2013), it is possible that BdMoV is also transmitted by the plasmodiophorid species. In this respect, we could not rule out the possibility that BdMoV studied in this study carries a deletion in the RT domain that may have occurred during preparation of its inoculum from C. quinoa inoculated mechanically.…”
Section: Discussionmentioning
confidence: 97%